The effects of the attributional style on the mathematics performance of senior secondary school students - Akolade Olubunmi Lapite; Jacobus Gideon Maree; Joyce Jordaan (South African Journal of Education, 2022)
The purpose of this study was to explore the effects of the attributional style on the mathematics performance of senior secondary school students. The study involved a sequential explanatory mixed-method approach (QUANTITATIVE + qualitative). The quantitative part of the study involved 300 students drawn from 2 schools chosen in 2 education districts in Lagos State, Nigeria. The major data generation instruments for the study were the Attributional Style Questionnaire (ASQ), the mathematics performance scores of students, and focus-group interviews. Focus-group interviews with 20 students (10 students per school) were used in the qualitative part of the study. Quantitative data were analysed by calculating correlation coefficients, conducting multiple regression analyses, and performing a one-way analysis of variance to compare the subscales across gender and socio-economic status. Conversation analysis was used to analyse the qualitative data generated. The findings reveal no significant relationships between the attributional style and mathematics performance. Gender-based differences were found in the stability and globality scales, students’ socio-economic status, and their attitudes towards mathematics. Future research on all the variables used in this study could be replicated on different samples. Researchers could consider exploring the use of an attributional style questionnaire on academic issues using a similar sample as in this study.